Lost Without It How GPS is more than just navigation - McAlister, Chris (Open textbook library., 2023)
The navigation that we get from GPS is just a tiny component of how it impacts our lives - from banking to mapping to just knowing where stuff is, it's now a critical part of how humanity functions. This book takes you through all the basics of how GPS works, kind of like a how-to, just in case zombies take out all those smart scientists that keep it all running!